Effect of swamp Eel (Monopterus albus) plasma on the quality of tilapia (Oreochromis mossambicus) Surimi - Nopianti, Rodiana; Chasanah, Ekowati; Sukarno,; Suhartono, Maggy Thenawidjaja (Penerbit Universiti Kebangsaan Malaysia, 2023)
The effects of crude plasma and ethanol-extracted of swamp eel plasma at different concentrations (0, 0.25, 0.5, 0.75, 1, 1.5, 2 mg/g) as inhibitor protease in the quality of tilapia (Oreochromis mossambicus) surimi were investigated. The parameters analyzed were gel strength, expressible moisture, whiteness, microstructure, protein solubility, hydrolysis pattern of surimi by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, percent inhibition, and zymogram. The results showed that ethanol-extracted plasma could maintain gel strength, expressible moisture, microstructure, protein solubility, and percent inhibition in lysis of tilapia surimi from protease activity that caused formation of modori structure better than crude plasma. The whiteness decreased as the concentration of plasma used increased. SDS-PAGE for hydrolysis pattern analysis showed that the effectiveness of crude plasma as a protease inhibitor decreased as the concentration increased. There was an increase in the inhibition of protease in the ethanol-extracted plasma at a concentration of 1.5 mg/g. It suggested that the crude plasma contained an internal protease enzyme that might interfere with the reduced myosin intensity.